صراع العتمة ، دراسة لحيوان الوحش في مواجهات الليل(*)(للشعراء المخضرمين) (University of Mosul-college of Basic Education, 2011)
يحاول هذا البحث جلاء أهم معالم مشاهد صراع العتمة لحيوان الوحش في مواجهات الليل ، والكشف عن بواعث هذا الصراع في وعي الشاعر المخضرم (عصر ما قبل صدر الإسلام) ، وتحقق ذلك من خلال التوحد الزماني والمكاني وفق منهج القراءة التحليلية لنماذج مختارة عبر رؤية نقدية تتمحور حول هذا الحيوان الوحشي الذي صار رمزاً مشحوناً بدلالات تراثية حضارية تحكي قصة زمن توازى مع خط المأساة الإنسانية المتمثلة بالموت . ومن ثم الكشف عن جدليات الحياة المتصارعة في الذات الإنسانية ، لتأتي صورة الصراع هذه متكاملة نموذجية تحكي قصة إنسان الصحراء والجدب والفناء من خلال نصوص انتقائية تحكي حواراً مع الكائنات .This study attempts to manifest the mist important features of the scenes related to wild animals' darkness struggle in night confrontations and revealing the motives of this struggle in the poets' consciousness in the early Islamic age . This was accomplished by the temporal and spatial unification in accordance with the analytical reading of some selected samples through a critical point of view that is focused on the wild animal which has become a symbol which carries cultural and civilizational denotations that narrate a story of a time that is parallel with the human tragedy represented by death . Then the study uncovered the controversies of life in struggle within the human himself so the image of this struggle comes to the surface as typical and complete to narrate the story of desert inhabitants , berrenness and extinction .